Highly Sensitive Immunochromatographic Identification of Tetracycline Antibiotics in Milk - N. A. Taranova; A. S. Kruhlik; E. A. Zvereva; V. V. Shmanai; I. I. Vashkevich; D. A. Semyonov; S. A. Eremin; A. V. Zherdev; B. B. Dzantiev (International Journal of Analytical Chemistry)
A rapid immunochromatographic assay was developed for the control of tetracycline (TC). The assay is based on the competition between immobilized TC-protein conjugate and TC in a tested sample for binding with polyclonal anti-TC antibodies conjugated to colloidal gold during the flow of the sample along a membrane strip with immobilized reactants. Conjugation of colloidal gold and the total immunoglobulin (IgG) fraction of polyclonal antibodies was used to increase the assay sensitivity to ensure low content of specific antibodies in the conjugate. This allowed effective inhibition of free TC and conjugate binding in the strip test zone. Photometric marker registration allows control of the reduction of binding, thereby enhancing detection sensitivity. The proposed assay allows TC to be detected at concentrations up to 20 ng/mL, exceeding the limit of detection of the known analogues, in a wide working range (more than two orders) of 60 pg/mL to 10 ng/mL, ensured through the use of polyclonal antibodies. The assay time is 10 min. The efficiency of the designed assay is shown to identify TC in milk; the degree of recovery of TC ranges from 90 to 112%. The precision of the concentrations measurements was no more than 10%.